Late works of Mou Zongsan : selected essays on Chinese philosophy - Mou, Zongsan (Modern Chinese philosophy, 2014)
In Late Works of Mou Zongsan, Jason Clower publishes English translations of this most famous and influential of modern Chinese philosophers for the first time. In essays chosen for their clarity and approachability, this leading contemporary Confucian speaks on the topics that best define his career: the future of Chinese culture and philosophy, the unique achievements of Confucianism, the place of Buddhism and Daoism in Chinese culture, and the possibility of a new partnership between Chinese and Western thought.